Determinants of desire for more children among women in Ethiopia - Mitiku Wale Muluneh; Yikeber Abebaw Moyehodie (BMC, 2021)
Abstract Background Desire for more children has an impact on couple's fertility behaviors. It can be a precursor of actual fertility performance. However, the desire for more children is declining over time in Ethiopia. Therefore, this study aimed to identifying the determinants of the desire for more children among women in Ethiopia. Methods The 2016 Ethiopian Demographic and Health Survey data were used for the analysis. The sample consisted of 15,683 women. The binary logistic regression model was used to assess the determinants of desire for more children among women in Ethiopia. The results are presented as crude odds ratios (COR) and adjusted odds ratios (AOR) together with their corresponding 95% confidence intervals. Results No education (having no formal education) (AOR = 1.85, 95% CI 1.61-2.13), attained primary education (AOR = 1.62, 95% CI 1.43-1.83), age at first marriage 10-19 years (AOR = 1.80, 95% CI 1.27-2.54), Orthodox religion (AOR = 1.48, 95% CI 1.01-2.19), Catholic religion (AOR = 2.15, 95% CI 1.17-3.97), Muslim religion (AOR = 1.70, 95% CI 1.15-2.50), living in Amhara (AOR = 1.45, 95% CI 1.18-1.78), Oromia (AOR = 2.10, 95% CI 1.73-2.54), Benishangul (AOR = 1.17, 95% CI 1.01-1.45), SNNPR (AOR = 1.30, 95% CI 1.05-1.60), Gambela (AOR = 1.25, 95% CI 1.02-1.57), Harari (AOR = 2.24, 95% CI 1.82-2.76), ideal number of children four or fewer (AOR = 0.47, 95% CI 0.42-0.53), number of living children four or fewer (AOR = 2.12, 95% CI 1.90-2.37), and not use of contraceptives (AOR = 1.51, 95% CI 1.35-1.68) were associated with a higher desire for more children. Conclusion This finding showed that the age of women, educational level, age at first marriage, religion, region, occupation, ideal number of children, number of living children, and use of contraceptives were significant determinants of desire for more children. Therefore, it is important to adopt programs to encourage the desire for more children, implement policies in an attempt to increase the total fertility rate in Ethiopia ought to critically consider these factors. Moreover, continuous education and knowledge on reproductive health will help for better fertility behaviour for the women.